Managing Macrophomina phaseolina causing charcoal rot of sunflower (Helianthus annus) by soil amendment - UTPAL DEY and D.P. KULDHAR, A.P. SURYAWANSHI*, V.P. MULE, K.T. APET (Indian Phytopathology, 2015)
The pot culture (screen house) studies were undertaken to manage charcoal rot (Macrophomina phaseolina) disease applying organic and inorganic amendments on sunflower (Helianthus annus L.). Of the 11 amendments tested, neem seed cake soil application (preventive and curative) @ 50g/kg potting mixture was found most effective with significantly highest seed germination (85.00 and 71.67%); least pre-emergence (15.00 and 28.33%), post-emergence (22.66 and 34.92%) and average (18.83 and 31.63%) mortality. There was significantly highest reduction in pre-emergence (78.57 and 59.52%), post-emergence (70.03 and 55.62%) and average (74.30 and 57.57%) mortality, respectively in preventive and curative methods. All the test amendments improved growth parameters, viz. root length, shoot length and vigour index in sunflower cv. KBSH-44. However, highest root length (14.10 and 13.60 cm), shoot length (26.53 and 24.73 cm) and vigour index (3453.55 and 2747.11) were recorded with neem seed cake, respectively in preventive and curative methods, followed by the amendments, viz. cotton seed cake, groundnut cake and sunflower cake.